Children with speech sound disorder: comparing a non-linguistic auditory approach with a phonological intervention approach to improve phonological skills - Murphy, Cristina F. B.; Pagan-Neves, Luciana O.; Wertzner, Haydée F.; Schochat, Eliane (Frontiers in Psychology, 2015)
This study aimed to compare the effects of a non-linguistic auditory intervention approach with a phonological intervention approach on the phonological skills of children with speech sound disorder. A total of 17 children, aged 7-12 years, with speech sound disorder were randomly allocated to either the non-linguistic auditory temporal intervention group (n = 10, average age 7.7 ± 1.2) or phonological intervention group (n = 7, average age 8.6 ± 1.2). The intervention outcomes included auditory-sensory measures (auditory temporal processing skills) and cognitive measures (attention, short-term memory, speech production and phonological awareness skills). The auditory approach focused on non-linguistic auditory training (eg. backward masking and frequency discrimination), whereas the phonological approach focused on speech sound training (eg. phonological organisation and awareness). Both interventions consisted of twelve 45-minute sessions delivered twice per week, for a total of nine hours. Intra-group analysis demonstrated that the auditory intervention group showed significant gains in both auditory and cognitive measures, whereas no significant gain was observed in the phonological intervention group. No significant improvement on phonological skills was observed in any of the groups. Inter-group analysis demonstrated significant differences between the improvement following training for both groups, with a more pronounced gain for the non-linguistic auditory temporal intervention in one of the visual attention measures and both auditory measures. Therefore, both analyses suggest that although the non-linguistic auditory intervention approach appeared to be the most effective intervention approach, it was not sufficient to promote the enhancement of phonological skills.